Secondary Victimization of Women Who Resume an Abusive Relationship - Oliveira, Jéssica; Roberto Pereira, Cícero (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Many studies have been conducted so as to understand what causes women to remain in abusive relationships and the barriers encountered in the process of leaving. We aimed to investigate the secondary victimization behaviors of women who resume an abusive relationship. Participants were 261 people aged between 18 and 72 years (M = 32.06; SD = 9.96), mostly female (83.9%). Participants were asked to read a vignette that described the relationship between John and Mary. However, there were three relationship outcomes based on which we manipulated information about the victim's behavior. The participants answered the questionnaire containing the Secondary Victimization Scale of Women Victims of Marital Violence (SVS), as well as socio-demographic information. The results found indicate that the participants perceived the victim's suffering more, devalue her and avoid her when she resumed the relationship. We realized that men blamed and devalued the victim more than women. Men also perceived less the victim’s suffering than women. Thus, our study presented empirical results that, when we refer to women victims of IPV, they are more victimized when they leave and resume the abusive relationship, which is described as the most frequent behavior of women.